Agile effort estimation in software development projects - case study - Maciej Łabedzki; Patryk Prominśki; Adam Rybicki; Marcin Wolski (The Central European Review of Economics and Management (CEREM), 2017)
Aim: The purpose of this paper is to identify common mistakes and pitfalls as well as best practices in estimating labor intensity in software projects. The quality of estimations in less experienced teams is often unsatisfactory, as a result of which estimation as part of the software development process is abandoned. The decision is usually justified by misunderstanding "agility". This article is part of the discussion on current trends in estimation, especially in the context of the new "no estimates" approach.Design / Research methods: The publication is a case study based on the experience of a mature development team. The author, on the basis of literature-based estimation techniques, shows good and bad practices, as well as common mistakes in thinking and behavior.Conclusions / findings: The key to correct estimation is: understanding the difference between labor intensity and time, ability to monitor performance, as well as how to analyze staff requirements for the team.Originality / value of the article: The publication helps to master confidence-boosting techniques for any estimation (duration, and indirectly, the cost of software development) where requirements are known, but mainly at the stage of project implementation (design and implementation).Limitations of the research: The work does not address the problems of initial estimation of projects, i.e. the estimation made in the early stages of planning. – – Cel: Celem niniejszej pracy jest wskazanie powszechnych błedoẃ i pułapek, a takzė sprawdzonych praktyk w zakresie estymacji pracochłonnosći w projektach programistycznych. Jakosćószacowanẃ mniej dosẃiadczonych zespołach jest czesto niezadowalajaca, wskutek czego estymacja jako element procesu wytwarzania oprogramowania jest porzucana. Decyzja zwykle uzasadniana jest błednie rozumiana "zwinnosćia". Artykuł wpisuje sie w dyskusje nad biezȧcymi trendami w zakresie szacowania, w szczegoĺnosći w konteksćie nowego podejsćia "no estimates".~Metodyka badan\': Publikacja ma forme studium przypadkoẃ opartego o dosẃiadczenia dojrzałego zespołu programistycznego. Autor, na podstawie znanych z literatury technik estymacji, wskazuje dobre i złe praktyki oraz czesto popełniane błedy w mysĺeniu i postepowaniu.~Wnioski: Kluczowe dla poprawnej estymacji okazuja sie: zrozumienie roźṅicy pomiedzy pracochłonnosćia i czasochłonnosćia, umiejetnosćḿonitorowania wydajnosći, a takzė sposob́ analizowania wymaganí sytuacja kadrowa zespołu.~Wartosćártykułu: Publikacja pomaga opanowact́echniki podnoszace poziom zaufania do wszelkich oszacowan\' (czasu trwania, a posŕednio - kosztu wytwarzania oprogramowania) tam, gdzie znane sa wymagania, jednak głoẃnie na etapie realizacji projektu (projekt i implementacja).~Ograniczenia: Praca nie porusza problemoẃ wstepnej estymacji przedsiewziec\', tj. estymacji dokonywanej na wczesnych etapach planowania.
Keywords: L86; 330; software development; estimation; effort; measurement; requirements engineering; story points; Scrum